Complex of Characteristic Zero in the Skew-Shape (8, 6, 3) / (u,1) where u = 1 and 2 - Abd-Alridah, Shaymaa N.; Hassan, Haytham R. (Iraqi Journal of Science, 2020)
In this work, we find the terms of the complex of characteristic zero in the case of the skew-shape (8,6, 3)/(u,1), where u = 1 and 2. We also study this complex as a diagram by using the mapping Cone and other concepts.